2019
DOI: 10.2495/sc190581
|View full text |Cite
|
Sign up to set email alerts
|

Construction Waste Management in Uae: An Exploratory Study

Abstract: In 2016, 9.68 million tons of solid waste were generated in Abu Dhabi alone where 67.8% was sent to dumpsites and landfills. In the same year, the construction and demolishing (C&D) industry produced 47% of the non-hazardous waste. This research aims to investigate the C&D waste management in UAE's construction industry, specifically in Abu Dhabi based on (a) official resources identifying authorized entities, regulations, implementation guidelines, and causes behind waste generation in UAE' C&D industry; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…The main pillars of waste management were examined to include legislative rules, environmental actions and economic incentives, while the barriers include resistance to the use of new construction methods, time limitations and high cost of investment in recycling and reusing [50] . The legislative rules in UAE require submitting waste management plan before construction activity and 30% diversion of waste into new products [51] , also the study revealed that most companies are looking to obtain Estidama certificate not to apply sustainability rules. Training of employees, good storage conditions and transportation of materials, integration between contractors and sub-contractors and use of prefabricated units can increase productivity and efficiency of construction industry [52] .…”
Section: United Arab Emiratesmentioning
confidence: 99%
“…The main pillars of waste management were examined to include legislative rules, environmental actions and economic incentives, while the barriers include resistance to the use of new construction methods, time limitations and high cost of investment in recycling and reusing [50] . The legislative rules in UAE require submitting waste management plan before construction activity and 30% diversion of waste into new products [51] , also the study revealed that most companies are looking to obtain Estidama certificate not to apply sustainability rules. Training of employees, good storage conditions and transportation of materials, integration between contractors and sub-contractors and use of prefabricated units can increase productivity and efficiency of construction industry [52] .…”
Section: United Arab Emiratesmentioning
confidence: 99%
“…In order to understand how a majority of the construction companies were able to properly manage their material wastes, their educational/training levels were assessed. It is reported that the method of waste disposal practised by a construction company may depend on the level of education or training gained by its waste management team (Hittini and Shibeika, 2019;Hasmori et al, 2020).…”
Section: Level Of Education and Waste Management Practicesmentioning
confidence: 99%
“…the individual or a team may use (Hittini and Shibeika, 2019). However, the impact of education on the use of waste management plans was profound and this should be encouraged.…”
Section: Level Of Education and Waste Management Practicesmentioning
confidence: 99%